Pelayanan Publik dalam Pelaksanaan Uji Kelayakan Kendaraan Angkutan Umum pada Dinas Perhubungan Kota Bandar Lampung - Nurhaliza Mutiara Jauhari; Nurmayani Nurmayani; Agung Budi Prastyo (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Public service in the transportation sector plays a strategic role in ensuring public safety and comfort, particularly through roadworthiness testing (Kir) for public transportation. This study aims to analyze the implementation of public services in roadworthiness testing at the Bandar Lampung City Transportation Agency and to identify the factors influencing its service quality. The research employs a qualitative approach, with data collected through interviews, observations, and documentation. The results indicate that the roadworthiness testing has been implemented systematically in accordance with statutory regulations, covering the stages of registration, technical inspection, result determination, and administrative completion. The application of technical inspections and on-field safety inspections (ramp checks) demonstrates the local government's commitment to improving public service quality and transportation safety. However, the implementation still faces several obstacles, including technological system disruptions, long waiting times, limited testing facilities and infrastructure, and a lack of understanding among some service users regarding the importance of roadworthiness. This study concludes that enhancing public services in roadworthiness testing requires strengthening the service systems, increasing human resource capacity, and raising public awareness to ensure services operate more effectively and remain oriented toward the public interest